Approximated computing for low power neural networks - Gian Carlo Cardarilli; Luca Di Nunzio; Rocco Fazzolari; Daniele Giardino; Marco Matta; Mario Patetta; Marco Re; Sergio Spanò (Universitas Ahmad Dahlan, 2019)
This paper investigates about the possibility to reduce power consumption in Neural Network using approximated computing techniques. Authors compare a traditional fixed-point neuron with an approximated neuron composed of approximated multipliers and adder. Experiments show that in the proposed case of study (a wine classifier) the approximated neuron allows to save up to the 43% of the area, a power consumption saving of 35% and an improvement in the maximum clock frequency of 20%.